Genomic stability in the archaeae Haloferax volcanii and Haloferax mediterranei. - López-García, P (1995)
Through hybridization of available probes, we have added nine genes to the macrorestriction map of the Haloferax mediterranei chromosome and five genes to the contig map of Haloferax volcanii. Additionally, we hybridized 17 of the mapped cosmid clones from H. volcanii to the H. mediterranei genome. The resulting 35-point chromosomal comparison revealed only two inversions and a few translocations. Forces known to promote rearrangement, common in the haloarchaea, have been ineffective in changing global gene order throughout the nearly 10(7) years of these species' divergent evolution.